Pelatihan Mesin Industri Pakan Ikan Berbasis PLTS 2 WP di Desa Selika 2 Kecamatan Tanjung Kemuning Kabupaten Kaur: PLTS 2 WP Based Fish Feed Industry Machine Training in Selika 2 Village, Tanjung Kemuning District, Kaur Regency - Khairul Amri; Yanolanda Suzantry Handayani; Hendri Hestiawan; Hardiansyah Hardiansyah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Selika 2 Village, Tanjung Kemuning District, Kaur Regency is located in Bengkulu Province in the south, where many fish farming industries have been built in Selika 2 Village due to the high unemployment rate. Many fish farming industries were built to reduce the unemployment rate in Selika 2 Village. However, the obstacle of the fish farming industry is the high price of fish feed, and the small fish feed industry needs help to afford it, so the price of fish being sold is high, and eventually, many industries are closed. Even though the Natural Resources (SDA) owned in Selika 2 Village are numerous, for example, corn, cassava, rice, and golden snails, widely cultivated in the rice fields. This natural resource can be utilized and processed into high-protein fish feed. So for that, our Kosabangsa service team donated several fish feed industry machines with a PLTS power source of 2 MWP, the method of this service is a team of experts providing training on running feed industry machines. The aim of this dedication is that in the future, in Selika Village, a fish feed industry can be built where the price of fish feed can be below the market price of Rp. 5,000,-/kg.